Evaluasi Efektivitas Sistem Administrasi Layanan Coating di Clean N Tidy dengan Metode Pieces - Wildatur Rohmah; Agus Budiyantara; Sandri Sagitarius Sarumaha (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Digital transformation has become a crucial need for businesses, including the automotive Service sector. However, Clean N Tidya vehicle coating Service enterprisestill relies on a manual administrative system, which causes various issues in Service effectiveness. This study aims to evaluate the administrative system used in Clean N Tidy’s coating Services using the PIECES framework, which includes six aspects: Performance, Information, Economics, Control, Efficiency, and Service. A qualitative descriptive approach was applied, with data collected through direct observation, semi-structured interviews, and questionnaires distributed to staff and customers. The analysis revealed that the current manual system is rated very poor across all PIECES indicators. Low Performance was evident in delayed data recording, inaccurate Information, and inefficient time and cost management. The manual system also lacks sufficient Control mechanisms, leading to administrative errors and limitations in Performance monitoring. These weaknesses negatively impact Service quality and hinder managerial decision-making. Based on these findings, the study recommends developing an integrated digital administration system to support more accurate, real-time, and efficient data management. Such a system is expected to enhance Service quality and improve the business's competitiveness.